The moving chord method for determining the curvature of the track axis - Władysław Koc (Przegląd Komunikacyjny)
Abstract: The paper adresses the issue of determining the curvature of the axis of the railway track in order to enable the determination of the geometrical characteristics of the measured route. A new concept of determining the curvature was used by the method of changing the angles of inclination of a moving (virtual) chord based on the knowlege of the Cartesian coordinates of a given region of the route. The verification of the proposed method, carried out on unambiguosly defined model geometric track layouts, showed the complete agreement of the obtained curvature diagrams with the diagrams constituting the basis for obtaining the corresponding geometric solution. The use of the moving chord method to determine the curvature of the operated railway track showed that the obtained curvature plots clearly differ from those for model layouts; they have a less regular, oscillating character, which results from the track deformation and measurement error. However, this does not prevent the possibility of estimating the basic geometrical parameters of the measured layout on this basis. Keywords: railroad; curvature of the track axis; verification of a new calculation method; determination of application possibilities